تحولات المركز الذكوري بين التوازي والتنافر: قراءة في رواية (خمس نساء ) لحنان المسعودي - إبراهيم, سامان جليل (Al-Adab Journal, 2019)
the novel of five women talks about the cultural dimension which relates to cultural drift and its criticism within the text space, as it has emerged in this novel a number of cultural patterns and formats that are controlled in the profiling system, ideology, hauling prominent elements that has been revealed according to the vision of modern cultural criticism ,and the way of exploring these drifts considered an important aspect in this novel, and this research aims to touch a male drifts forms parallel and divergent towards the other, and also it has been addressed this aspect with its intellectual, cultural and artistic dimensions in an attempt to explore the imaginary world that the writer dream of it and what it requires from the demolition of the building and refused to accept, the writer inspired herself in her writing to reveal unspoken and hidden and accumulated over the time to declare it explicitly in her dialogue or conflict with man.